A continuous composition spread approach towards monolithic, wavelength-selective multichannel UV-photo-detector arrays. Issue 1633 (2014) - von Wenckstern, H.; Zhang, Z.; Lenzner, J.; Schmidt, F.; Grundmann, M.
ABSTRACT: Continuous composition spread (CCS) methods have been very successfully used for exploiting and optimization of new material systems. Concerning sample growth by pulsed-laser deposition (PLD) approaches towards thin films with a CCS are involved, here movable masks for partial shadowing of the substrate and multiple targets are needed to obtain linearly varying changes of composition. Here we make use of an approach allowing deposition of thin films with CCS at high growth rates by using segmented PLD targets. We describe how this approach can be used to fabricate monolithic, wavelength-selective multichannel UV-photo-detector arrays.